The impact of artificial intelligence on intellectual property: A study analyzed according to Saudi sources and Laws - Abdulaziz Saeed Aljuhani (International Journal of Law Research and Studies, 2025)
The research initially addressed the nature of artificial intelligence, its types and forms. It then addressed the impact of artificial intelligence on Saudi commercial regulations, discussing its impact on intellectual property. The research adopted two research approaches: a descriptive approach and an analytical approach. The descriptive approach involves identifying the legal texts related to the subject of the study and highlighting them in the study. It also highlights the judicial rulings related to the subject of the study. The analytical approach involves using the descriptive approach to extract and clarify legal provisions, followed by the analytical approach, which analyzes these legal provisions and extracts legal analyses consistent with the text of the legal article. The research reached several conclusions, the most important of which is that artificial intelligence outputs are not considered authorship or inventorship. It also reached several recommendations, the most important of which is the need to clarify the definition of a natural person.